Nucleotide excision repair in chronic neurodegenerative diseases (2013)
Impaired DNA repair involving the nucleotide excision repair (NER)/transcription-coupled repair (TCR) pathway cause human pathologies associated with severe neurological symptoms. These clinical observations suggest that defective NER/TCR might also play a critical role in chronic neurodegenerative disorders (ND), such as Alzheimer's and Parkinson's disease. Involvement of NER/TCR in these disorders is also substantiated by the evidence that aging constitutes the principal risk factor for chronic ND and that this DNA repair mechanism is very relevant for the aging process itself. Our understanding of the exact role of NER/TCR in chronic ND, however, is extremely rudimentary; while there is no doubt that defective NER/TCR can lead to neuronal death, evidence for its participation in the etiopathogenesis of ND is inconclusive thus far. Here we summarize the experimental observations supporting a role for NER/TCR in chronic ND and suggest questions and lines of investigation that might help in addressing this important issue. We also present a preliminary yet unprecedented meta-analysis on human brain microarray data to understand the expression levels of the various NER factors in the anatomical areas relevant for chronic ND pathogenesis. In summary, this review intends to highlight elements supporting a role of NER/TCR in these devastating disorders and to propose potential strategies of investigation. © 2013 Elsevier B.V.